2013
DOI: 10.1080/13548506.2012.701755
|View full text |Cite
|
Sign up to set email alerts
|

The psychological benefits of recreational running: A field study

Abstract: Running yields positive changes in affect, but the external validity of controlled studies has received little attention in the literature. In this inquiry, 50 recreational runners completed the Exercise-Induced Feeling Inventory (Gauvin & Rejeskí, 1993) before and after a bout of self-planned running on an urban running path. Positive changes were seen in all four measures of affect (p < .001). Multivariate regressions were performed to examine the contribution of four exercise characteristics (i.e., duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Running generates numerous benefits to improve health and prevent the problems associated with a sedentary lifestyle. Running is an activity characterized by a health-oriented approach, popularity and accessibility, because it has few economic conditions or specific infrastructures for its practice and can be practised anywhere, at any time [7,8]. Although this activity attracts a large number of practitioners of all ages, there are problems associated with its abandonment, due to injuries, motivational deficiencies and even negative addictions.…”
Section: Introductionmentioning
confidence: 99%
“…Running generates numerous benefits to improve health and prevent the problems associated with a sedentary lifestyle. Running is an activity characterized by a health-oriented approach, popularity and accessibility, because it has few economic conditions or specific infrastructures for its practice and can be practised anywhere, at any time [7,8]. Although this activity attracts a large number of practitioners of all ages, there are problems associated with its abandonment, due to injuries, motivational deficiencies and even negative addictions.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the second part of the model-pertaining to the intensity of exercise(s)-may be questionable. A number of past investigations have revealed that exercise characteristics have little role in mediating the psychological benefits (Rendi et al, 2008;Szabo, 2003a;Szabo & Á brahám, 2012). Research has also demonstrated that an equal-toexercise duration, low-or no-effort activity, like mindful exercises, music, or humor trigger identical, or greater, changes in affect than exercise (Netz & Lidor, 2003;Szabo, 1988Szabo, , 2003bSzabo, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence indicates that expectations play a role in some of the outcomes of common activities such as running (Berger, Owen, Motl, & Parks, 1998;Kwan et al, 2017;Szabo & Abraham, 2013) and cycling (Helfer et al, 2014;Mothes et al, 2017). For example, Helfer et al (2014) explored the role of expectancy effects on mood following 10-minutes of light-intensity cycling.…”
Section: Accepted Manuscript Expementioning
confidence: 99%